Customer Segmentation Using K-Means Algorithm As A Basis For A Marketing Strategy In The Store Rumah Tua VAPE: Customer Segmentation Using K-Means Algorithm As A Basis For A Marketing Strategy In The Store Rumah Tua VAPE - Fadly, Rahmat; Wahyudin, Iwan; Winarsih, Winarsih (Jurnal Mantik, 2020)
The development of the industrial system at this time more and more. Competition in the business world is increasingly stringent and requires business people to create good marketing strategies, one of which utilizes transaction data from Old Vape store companies is a company engaged in the field of electronic cigarettes. But the lack of observation in choosing customer data is less effective. And to overcome this problem can use data clustering analysis using k-means algorithm. And clustering techniques are functional in data mining, data mining algorithms are grouping a lot of data into several data groups or clusters. The data used is taken from the Vape Old House Store customer data, which results in a type of data grouping, namely customer segmentation for basic strategies in the Vape Old House Store so that customer data is not in vain.